The Effect of Crafting and Entrepreneurship Learning on Students’ Entrepreneurship Interest at SMP Negeri 07 Rarowatu Utara, Indonesia - Serti Serti (USN Scientific Journal, 2023)
This study aims to determine the effect of craft learning on the interest in entrepreneurship in class IX students of SMP Negeri 07 Rarowatu Utara. This research is an Ex Post Facto research with a quantitative descriptive approach. The population in this study were 29 students of class IX at SMP Negeri 07 Rarowatu Utara. Data on craft learning was taken using a questionnaire instrument. Test the validity of the instrument using the Product Moment correlation and test the reliability using Cronbach's Alpha. Test the requirements of data analysis using the normality test and linearity test, while for testing the hypothesis using a simple regression analysis technique. The results showed that: (1) Crafts were in the very high category 6%, high category 17%, medium category 41%, low category 21% and very low category 15; (2) Interest in Entrepreneurship very high category 17%, high category 29%, Moderate category 33%, low category 15% and very low category 6%; (3) the results of testing the hypothesis show that there is a positive and significant influence between the effect of craft learning on interest in entrepreneurship.